A Single Case Evaluation of Osteoarthritis and its Management Through Panchkarma - Silswal, Meenakshi; Arse , Reshma; Yadav, Himani; Sharma, K K; Sharma, Parul (International Research Journal of Ayurveda & Yoga, 2024)
Osteoarthritis is a degenerative joint disease and also known as a wear and tear disease. It is extremely prevalent in society and is a major cause of disability. Osteoarthritis can be correlated with Sandhigata Vata based on similarities in information reviewed from Ayurveda and modern literature. Sandhgatavata is one such condition, which usually starts with ageing and has become common in the society. It is disease which appears mostly in the early forties but due to over use of joint, trauma, deficient diet and obesity this disease has become now prevalent in young generation too. Hence, not only treating Sandhigata Vata is important but equal emphasis must be given to prevent early degeneration and related changes. In the present study the treatment of Male patient having symptoms of Sandhigata Vata treated with Ayurvedic medication along with Panchkarma therapies. No such complication was found during the treatment and significant improvement was observed in sign and symptoms. It is important to treat Osteoarthritis effectively using a multidisciplinary approach and Panchakarma provides such approach to the patients.